Comparative Analysis of Chicken Manure and NPK Fertilizer on Profitability and Environmental Impact in Food Crop Farming in Tomohon - Rumondor, Fadly Steven Jefry; Kumolontang, Geyby; Lintong, Heibert (Jurnal Ilmu Pertanian, 2026)
Chicken manure improves soil fertility by adding organic matter and enhancing soil structure, while NPK fertilizer provides fast, readily available nutrients. This study compared both fertilization strategies in rice and corn farming in Tomohon City, focusing on profitability, production costs, environmental impacts, and factors influencing farmers’ choices. A comparative observational method was used with 120 farmers selected through simple random sampling. Results showed that NPK fertilizer generated higher profits in corn farming, but no significant difference was found in rice. Meanwhile, chicken manure resulted in more cost-efficient production. Environmentally, chicken manure improved soil quality by increasing pH toward neutral, raising organic carbon (>2.7%), enhancing cation exchange capacity, and reducing nitrate residues and exchangeable aluminum—key indicators of long-term soil health in volcanic soils. In contrast, NPK fertilizer contributed to soil degradation, including declining pH, reduced organic matter, and accumulation of nitrate and exchangeable aluminum, which may harm root development and increase groundwater contamination risks. Farmers’ fertilizer choices are influenced by technical, economic, institutional, and socio-cultural factors. Overall, the findings highlight the importance of integrated fertilization strategies combining organic and inorganic inputs to balance short-term profitability and long-term sustainability. Policy efforts should focus on promoting integrated nutrient management, strengthening extension services, and providing incentives for environmentally sustainable practices to improve farm outcomes while preserving soil health.